Cultural Biases in Migration: Estimating Non-Monetary Migration Costs - Oliver Falck; Alfred Lameli; Jens Ruhose (Institute for the Study of Labor (IZA), 2015)
Ever since Sjaastad (1962), researchers have struggled to quantify the psychic costs of migration. We monetize psychic cost as the wage premium for moving to a culturally different location. We combine administrative social security panel data with a proxy for cultural difference based on historical dialect dissimilarity between German counties. Conditional on geographic distance and pre-migration wage profiles, we find that migrants demand a (indexed with respect to local rents) wage premium of about 1 (1.5) percent for overcoming one standard deviation in cultural dissimilarity. The effect is driven by males and those who earn above average occupational wages before migration, more pronounced for geographically short moves, and persistent over time.
Keywords: D51; J61; R23; 330; migration costs; culture; internal migration; psychic cost